Molecular thin films on solid surfaces mechanisms of melting - Feng, Haijun (Langmuir : the ACS journal of surfaces and colloids, 2012)
We use molecular dynamics simulations to study the melting of pentane and hexane monolayers adsorbed on the basal plane of graphite. For both of these systems, the temperature-dependent structures and the melting temperatures agree well with experiment. A detailed analysis reveals that a mechanism involving the promotion of molecules to the second layer underlies melting in these systems. In the second-layer promotion mechanism, a small fraction of molecules transition into the second layer around the melting temperature, leaving vacant space in the first layer to facilitate disordering. The second-layer promotion mechanism arises because of the weaker molecule-surface interaction in our study than that in previous studies. The weaker molecule-surface interaction is consistent with experimental temperature-programmed desorption studies